2017
DOI: 10.4172/2155-6113.1000733
|View full text |Cite
|
Sign up to set email alerts
|

Under Nutrition Status and Its Determinants among Adult HIV and AIDS Clients Enrolled on Antiretroviral Therapy at Nigest Elleni Mohammed Memorial Hospital, Southern Ethiopia

Abstract: Background: HIV/AIDS and malnutrition effects are interrelated and exacerbate one another in a vicious cycle. HIV specifically affects nutritional status by increasing energy requirements, reducing food intake and adversely affecting nutrient absorption and metabolism. In spite of the number of People Living with HIV ever enrolled on ART increases significantly in Ethiopia. Nutritional care and other supports which help for the success of treatment received insufficient attention. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Also, this study indicated that people living with HIV on ART who did not receive nutritional counseling were associated with undernutrition. is is similar to studies from Ethiopia [40], India [41], and Honduras [42], in which nutritional counseling improves dietary feeding practices.…”
Section: Discussionsupporting
confidence: 84%
“…Also, this study indicated that people living with HIV on ART who did not receive nutritional counseling were associated with undernutrition. is is similar to studies from Ethiopia [40], India [41], and Honduras [42], in which nutritional counseling improves dietary feeding practices.…”
Section: Discussionsupporting
confidence: 84%
“…[32] The study also found that that PLWHA who did not receive dietary counseling were likely to be malnourished. This is consistent with a study done in India [33]; in Honduras [34] and in Ethiopia [18,35] which indicated that those PLWHA on ARV who received nutritional counseling had lower undernutrition due to improved dietary feeding practices. This can be explained that those who attended dietary counselling during care visits acquired more knowledge on nutritious food such as adequate amount, quality and diversity.…”
Section: Figure 1 Prevalence Of Undernutrition In People Living With ...supporting
confidence: 91%
“…Based on several studies, the determinants of undernutrition are socio-economic status, level of education, unemployment, age, sex, marital status, CD4 count, depression, alcohol consumption, smoking tobacco, substance use, previous opportunistic infections, gastrointestinal symptoms, HIV/AIDS stage, medication adherence, duration of treatment, food insecurity, poor dietary diversity, family or social support. [7,8,11,[15][16][17][18] The high undernutrition rate and HIV/ AIDS are among the main public health concerns especially on the health systems of SSA, despite considerable control made in the last decade. Complication due to undernutrition among PLWHA is a major challenge of the HIV control efforts in low and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…This crisis has had a negative impact on social health and well-being, adult productivity, and adult survival. The HIV pandemic alarmingly elevated morbidity and mortality rates, which synergize when combined with malnutrition [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%